Investigation of the corrosion inhibition properties of hexamine (HMTA) for mild steel in NaCl solution - Fathabadi Hadi Ebrahim; Mohammad Ghorbani (Zaštita Materijala)
An effective corrosion inhibitor for steel is Hexamine (HMTA). There have been few studies on its corrosion-inhibiting characteristics, particularly in NaCl solution. The electrochemical characteristics of HMTA performance in NaCl 3.5 wt% solution were examined during this study. Additionally, the properties of the HMTA film on the steel surface was investigated. When tested in NaCl solution, electrochemical results revealed that HMTA is a very efficient corrosion inhibitor for mild steel, with an efficacy of 92% at a concentration of 0.08 M. HMTA exhibited mixed type activity in terms of inhibition, according to the findings. Due to the physical adsorption of HMTA compound, as shown by the XRD results, an organic layer was formed as a strategy for HMTA inhibition. Adsorption of chloride ions as a corrosive factor is reduced by the HMTA films, according to EDS and thermodynamic studies.